262 The Missouri Show-Me-Select Replacement Heifer Program: II. Comparing pregnancy rates resulting from fixed-time artificial insemination based on reproductive tract score and estrous synchronization protocol. (7th December 2018) - Bonacker, R; Thomas, J; Locke, J; Knickmeyer, E; Decker, J; Poock, S; Patterson, D
Abstract: The Show-Me-Select Replacement Heifer Program has improved reproductive management of beef herds in Missouri through increased use of reproductive technologies. Field data collected in support of the program include an array of reproductive evaluations unique to the beef industry. Producers that enroll heifers in the program are required to follow detailed management guidelines and adhere to approved animal health regimens. Prebreeding evaluations are performed by licensed veterinarians four to six weeks prior to breeding, and each heifer is assigned a reproductive tract score (RTS: Scale 1–5). Pregnancy diagnoses must be performed within 90 d of the start of the breeding season. In recent years, participants in the program have relied heavily on fixed-time artificial insemination (FTAI) using one of three protocols designed to synchronize estrus. These protocos include: 7-day CO-Synch+CIDR, MGA-PG, and 14-day CIDR-PG. Data from 2010–2017 were compiled to evaluate relationships between RTS and pregnancy rates resulting from FTAI. Pregnancy rates were compared based on pubertal status of heifers (n = 35, 158) at the time prebreeding evaluations were performed, categorized as either: pre/peripubertal (RTS = 2 and 3) or; pubertal (RTS = 4 and 5). Heifers determined to have an infantile tract (RTS=1) were excluded. The results are shown in Table 1. These data support the practice of establishing prebreeding criteria for identification of heifers that are good candidates for a FTAI program and illustrate performance of the various protocols under field conditions.